Preferences for and potential impacts of financial incentives to install residential rooftop solar photovoltaic systems in Australia. (1st September 2019) - Zander, Kerstin K.; Simpson, Genevieve; Mathew, Supriya; Nepal, Rabindra; Garnett, Stephen T.
Abstract: Shifting the production of energy from fossil fuels to renewable resources contributes towards the reduction of greenhouse gas emissions needed for climate change mitigation. Many countries, including Australia, have had generous financial incentives in place to support households to adopt renewable energy technologies, such as rooftop photovoltaic solar panels. Given the increasing reductions in, and eventually a shift, from subsidies to market-based mechanisms the trend of new solar panel adoption is unclear. Solar power is a particularly relevant climate change mitigation technology in Australia given the country's high insolation rates. Australia has one of the highest rates of residential solar adoption in the world with 20% of households having solar panels. This study uses Australia as a case study because of the range of incentives available and the potential impacts of changes in incentive policies which are already under way. To determine preferences for changes in incentives and to predict consumer choices for adopting solar panels under future policy changes, a choice model was applied. Results showed that about two-thirds of the respondents would be willing to install a photovoltaic system. Installation costs had the greatest influence on choice of a photovoltaic system, followed by a 10-year and a 5-year guarantee of being able to sell excess solar power to retailers, and a high feed-in-tariff. Being able to access an interest free loan did not affect respondents' choices, and up-front rebates were preferred to be at least AUD 4000. Income, education, knowledge about Australia's renewable energy polices and believing in environmental benefits of solar energy all positively influenced the willingness to install a photovoltaic system while age had a negative effect. Preferences for financial incentives varied significantly across respondents. About a third of respondents were sufficiently sensitive to costs and incentives that a substantial cut in subsidies would probably dissuade them from installing a photovoltaic system. Younger people and those knowledgeable about renewable energy policies preferred low installation costs but were not motivated by incentives. Factors likely to influence their decision-making included their level of electricity consumption, rising electricity prices and decreasing costs for storage systems, and they may conclude that solar photovoltaic systems pay off even without government subsidies, which are gradually being phased out. Highlights: Conducted choice experiment across Australian public. Installation costs main driver for decision to install solar PV in future. Strong preference for longer period of time to sell solar energy. The amount of the tariff for solar energy (FiT) is third driver. Younger and knowledgeable likely to install PV independently of incentives.